Analysis of Project Supervision Performance in the Water Resources Sector of the Public Works and Spatial Planning Service of Central Maluku Regency - Tuankotta, Sarbun; Zacharias , Tehubijuluw; Laurens, Samson (Syntax Corporation Indonesia, 2024)
This research aims to determine and analyze the implementation of the Water Resources Project for the Public Works and Spatial Planning Department of Central Maluku Regency. This research uses a descriptive qualitative approach. Carrying out research in the Water Resources Sector of the Public Works and Spatial Planning Department of Central Maluku Regency for 2 (two) months, namely July to September 2023. The data analysis technique in this research uses the Miles and Huberman model. The results of the research concluded that supervision of the implementation of the Water Resources Project for the Public Works and Spatial Planning Department of Central Maluku Regency was reviewed from the indicators of performance, conformance, aesthetics, time, timelines, consistency, accessability & convenience, accuracy, responsiveness, reliability, communication, security, competence. in accordance with applicable regulations and standard operating procedures